The messy reality of organised crime research - FINDLAY, Mark (Institutional Knowledge at Singapore Management University, 2010)
The analysis starts out by confronting and exposing the ideological motivations for dualism in conventional organised crime research. In order to suggest a cognitive pathway beyond this restrictive normative frame, it is essential to appreciate its potency and resilience. Law enforcement language buoyed up by popular culture representations of gangs, syndicates and crime bosses have become the accepted starting point for much research in the field. Research from this perspective, we suggest, plays its own part in organised crime mystification and as such retards the critical utility of enterprise theory. Next the paper shows how distracted and distorted theorising infects research methodology and its conclusions. We advance an alternative relationship between theorising and method so that resultant analysis approach crime business as it is, and not as law enforcement perspectives want us to believe it to be. The paper concludes by propounding an integrated theoretical perspective without the distraction of duality. Based on our field experience, we formulate and introduce the two-napkins methodology which is a dynamic, interactive and multi-dimensional framework for understanding criminal enterprise.